It happened one night - Adams, Samuel Hopkins 1871-1958; Adams, Samuel Hopkins 1871-1958 (<<The>> Criterion Collection, 2014)
"Opposites attract with magnetic force in this romantic road-trip delight from Frank Capra, about a spoiled runaway socialite (Claudette Colbert) and a roguish man-of-the-people reporter (Clark Gable) who is determined to get the scoop on her scandalous disappearance. The first film to accomplish the very rare feat of sweeping all five major Oscar categories (best picture, best actor, best actress, best director, and best screenplay), "It happened one night" is among the most gracefully constructed and edited films of the early sound era, packed with clever situations and gags that have entered the Hollywood comedy pantheon and featuring two actors at the top of their game, sparking with a chemistry that has never been bettered." [criterion.com]
Aspect ratio 1.33:1. - New 4K digital restoration
Orig.: USA 1934
Enth. "Screwball comedy?", a new conversation between critics Molly Haskell and Phillip Lopate ; interview with Frank Capra Jr. from 1999 ; "Frank Capra's american dream", a 1997 feature-length documentary about the director's life and career ; new digital transfer of Capra's first film, the 1921 silent short "Fultah Fisher's boarding house", with a new score composed and performed by Donald Sosin ; American Film Institute tribute to Capra from 1982 ; Trailer ; an essay by critic Farran Smith Nehme